Bringing cattle to full feed of grain rapidly (with and without Stilbestrol implants). - Koch, B.A.; Smith, E.F.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
Bringing cattle to a full feed of grain in the shortest time possible is one way to reduce the total time they require to reach market weight. Producers are always faced with the problem of bringing cattle on feed too fast and causing digestive upsets, which lengthen the feeding period. This study was designed to determine what advantage could be gained by mixing cottonseed hulls with the grain ration. One half the animals in the study were implanted with stilbestrol to secure further information as to its value.
Keywords: Beef; Stilbestrol; Intake; Grain